AN ANALYSIS OF THE LEVEL OF PROFESSIONALISM OF PERSONNEL IN THE APPLICATION OF TOTAL QUALITY MANAGEMENT APPROACH IN BUILDING MAINTENANCE PRACTICES - ABDULAZEEZ A.D.; ABBAS A.; IBRAHIM A. D. (Innovare Journal of Engineering and Technology, 2015)
The establishment and achievement of acceptable levels of quality in building maintenance projects has long been a problem. Despite significant amount of investigations have already been undertaken to examine quality failures and their causes, maintenance projects are still encountering numerous quality problems. Hence, this research was birthed by the urge to establish the degree by which building maintenance operations are undertaken in Nigerian universities with respect to the total quality management principles. The European Construction Institute (ECI) measurement matrix was adopted for establishing the degree. The sample size was calculated using Kish formula. 75 responses, which accounted for 99% of the total respondents, were received. For reasons of costs and security, three Universities in the north-central region of the country were surveyed. Based on the ECI classification, the selected Universities were graded under the status of Need Commitment to Overcome Resistanceâ€. Hence, it was recommended that Universities should employ competent personnel, and place high premium on quality factors like employee training, team workmanship in order to achieve acceptable quality management in their building maintenance practicesD